Insights into the blood, gut, and oral microbiomes in Chinese patients with myocardial infarction: a case-control study - Ikram Khan; Imran Khan; Ping Xie; Yu Xiaohui; Shengnan Lei; Tianzhu Song; Zhiqiang Li; Xiaodong Xie (BMC Microbiology)
Abstract Background Emerging evidence suggests that changes in the blood microbes might be associated with cardiovascular disease, especially myocardial infarction (MI). However, some researchers are questioning whether a true “blood microbiome” actually exists. They hypothesized that these microbes may translocate into the bloodstream from the gut or oral cavities. To test this hypothesis, we analyzed the microbial composition, diversity, and potential role in disease progression by comparing blood, gut, and oral microbiota profiles in a cohort of MI patients and healthy controls. Methods In this study, 144 samples, including blood, fecal, and saliva, were collected from twenty-four myocardial infarction patients and twenty-four healthy controls. These samples were analyzed using 16 S rRNA sequencing to characterize the microbial profiles across the three distinct microbial compartments. Differential analyses were conducted to find key differential microbiota for MI. Spearman’s rank correlation analysis was used to study the association between microbiota and clinical indicators. Results Our findings revealed striking microbial shifts across blood, gut, and oral compartments in MI patients compared to healthy controls. In the blood, we observed significant enrichment of the phyla Armatimonadota and Caldatribacteriota, alongside the genera Bacillus, Pedobacter, and Odoribacter. The gut microbiota of MI patients showed a notable increase in the phyla Proteobacteria, Verrucomicrobiota, Cyanobacteria, Synergistota, and Crenarchaeota, as well as the genera Eubacterium_coprostanoligenes_group, Rothia, Akkermansia, Lachnospiraceae_ NK4A136_ group, and Eubacterium_ruminantium_group. Meanwhile, the oral microbiota of MI patients was uniquely enriched with the phylum Elusimicrobiota and the genera Streptococcus, Rothia, and Granulicatella. These distinct microbial signatures highlight compartment-specific alterations that may play a role in the pathophysiology of MI. Additionally, LEfSe analysis identified 64 distinct taxa that differed across the three compartments. Of these, eight taxa were unique to blood, eighteen to the gut, and thirty-eight to the oral microbiota, all of which demonstrated significant associations with clinical markers of MI. Functional pathways were predicted and analyzed via KEGG annotation, but no statistically significant differences were found between MI patients and healthy controls in any of the microbiome compartments. Conclusion This study demonstrates significant alterations in the blood, gut, and oral microbiome profiles of MI patients, identifying specific bacterial taxa strongly associated with key markers of myocardial infarction. The unique microbial patterns detected in the blood provide compelling evidence for the existence of a stable core blood microbiome, highlighting its importance as a key contributor to cardiovascular health and disease progression.